2017
DOI: 10.23917/indigenous.v1i2.3072
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Coping Wanita Pekerja Formal Dan Informal Dalam Mengatasi Konflik Peran Ganda Di Banyumas

Abstract: Abstract. This study aims to determine differences in duel roles Keywords : conflict, coping strategies, formal workers, informal workersAbstrak. Penelitian ini bertujuan untuk mengetahui perbedaan konflik peran ganda antara wanita pekerja formal dengan wanita pekerja informal, dan untuk memperoleh temuan tentang strategi coping pada wanita pekerja formal dan wanita pekerja informal dalam menghadapi konflik peran ganda. Metode yang digunakan dalam penelitian ini adalah studi deskriptif dengan pendekatan mix me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Emotional focus coping by employees can reduce the level of negative emotions in responding to stressors. In line with the research Dwiyanti and Rahardjo (2016) found that the coping strategies used by formal female workers in the form of Emotion Based included: emotional control, regret because sometimes being in harmony with children, going out with family, venting problems with coworkers. Ben-Ari and Hirshberg's (2009) research found a strong and significant correlation between coping strategies and perceptions of conflict, the more positive the attitude towards conflict will use a more cooperative strategy in overcoming conflict.…”
Section: Discussionsupporting
confidence: 63%
“…Emotional focus coping by employees can reduce the level of negative emotions in responding to stressors. In line with the research Dwiyanti and Rahardjo (2016) found that the coping strategies used by formal female workers in the form of Emotion Based included: emotional control, regret because sometimes being in harmony with children, going out with family, venting problems with coworkers. Ben-Ari and Hirshberg's (2009) research found a strong and significant correlation between coping strategies and perceptions of conflict, the more positive the attitude towards conflict will use a more cooperative strategy in overcoming conflict.…”
Section: Discussionsupporting
confidence: 63%
“…Seseorang cenderung menggunakan PFC saat memiliki keyakinan jika tekanan yang dihadapi akan berubah apabila permasalahan yang menjadi sumber tekanan diatasi dan seseorang akan cenderung menggunakan EFC ketika ia mengatasi stres dengan mengontrol emosinya saja. 21 Pada masa usia dewasa akhir dosen perempuan paling banyak mengalami stres dengan tingkat stres sedang (21,2%). Pada masa usia dewasa awal maupun dewasa akhir, dosen perempuan telah terbiasa menjalankan rutinitasnya sebagai seorang pekerja dan ibu rumah tangga.…”
Section: Pembahasanunclassified
“…In this study, researchers will focus more on mothers who work in the formal sector. Dwiyanti and Rahardjo (2016) explained that the burden felt by women who work in the formal sector is higher than that of women who work in the informal sector. The burden in question is the rules regarding strict working hours, challenging work assignments, and the existence of work completion targets.…”
Section: Introductionmentioning
confidence: 99%